Heavy precipitation events in northwestern China induced by northeastward plateau vortex: Two cases comparison - Huang, Yujing; Ma, Xulin; Ma, Yue; Qing, Yiyu (Frontiers in Earth Science, 2022)
The plateau vortex is one of the dominant weather systems that modulate summer rainfall in northwestern China, a typical arid/semi-arid area worldwide. Two heavy rainfall cases in the summer of 2012 and 2013, accompanying the northeastward movement of plateau vortexes, are selected here. The role of plateau vortexes in these two cases is explored by diagnosing their moist potential vorticity, helicity, and convective clouds characteristics, using numerous data (ERA-Interim reanalysis, multi-sourced precipitation data, FY-2E satellite images). The plateau vortexes enhanced convective instability in the rainfall area by entraining upper-level dry and cold air, manifested as salient vertical gradients of moist potential vorticity and steep pseudo-equivalent potential temperature isolines. The rainfall occurred eastward relative to the vortex movement track and intensified on the left of cloud black body temperature (TBB) with larger gradients at the middle to late stages of the vortex life span. The generation of moisture helicity is dictated by the water vapor transportation, with the negative value concentrated in the water vapor-rich areas. Notably, the two cases differ in tracks, life spans, water vapor sources, and precipitation amounts, which may be attributed to large-scale circulation background, vertical vortex structure, and moisture condition.